Case Report: A novel PHOX2B p.Ala248_Ala266dup variant causing congenital central hypoventilation syndrome - Irina N. Artamonova; Anna M. Zlotina; Olga R. Ismagilova; Tatyana A. Levko; Natalia Yu Kolbina; Aleksandr V. Bryzzhin; Andrey P. Smorodin; Alexandr V. Borodin; Ekaterina A. Mamaeva; Anna A. Sukhotskaya; Ilya M. Kagantsov; Daria A. Malysheva; et al. (Frontiers Media S.A., 2023)
IntroductionCongenital central hypoventilation syndrome (CCHS) is a rare disease characterized by central alveolar hypoventilation and impaired autonomic regulation, caused by pathogenic variants of PHOX2B gene. More than 90% of patients have a polyalanine repeat mutation (PARM) in the heterozygous state, characterized by the expansion of GCN repeats and an increase in the number of alanine repeats, so that genotypes 20/24-20/33 are formed (the normal genotype is 20/20). The remaining 10% of patients harbor non-PARMs.Case descriptionWe present a clinical case of a girl with a novel PHOX2B heterozygous genetic variant in the exon 3: NM_003924.4: c.735_791dup, p.Ala248_Ala266dup. The duplication includes 16 GCN (alanine) repeats and 3 adjacent amino acids. Both clinically healthy parents demonstrated a normal PHOX2B sequence. In addition, the girl has a variant of unknown significance in RYR1 gene and a variant of unknown significance in NKX2-5 gene. The child's phenotype is quite special. She needs ventilation during sleep, and has Hirschsprung's disease type I, arteriovenous malformation S4 of the left lung, ventricular and atrium septal defects, coronary right ventricular fistula, hemodynamically nonsignificant, episodes of sick sinus and atrioventricular dissociation with bradycardia, divergent alternating strabismus, and oculus uterque (both eyes) (OU) retinal angiopathy. Two episodes of hypoglycemic seizures were also registered. Severe pulmonary hypertension resolved after appropriate ventilation adjustment. Diagnostic odyssey was quite dramatic.ConclusionDetection of a novel PHOX2B variant expands the understanding of molecular mechanisms of CCHS and genotype-phenotype correlations.